Analisis Dampak Pembangunan Gedung Terhadap Kinerja Jaringan Jalan Di Kecamatan Murung Pudak, Kabupaten Tabalong: Traffic Impact Analysis Of Building Development On Road Network Performance In Murung Pudak, Indonesia - Hidayat, Muya Ryan; Ridhani Noor Fauzi, Ahmad; Azhar, Muhammad (Media Ilmiah Teknik Sipil, 2026)
The development of buildings in urban areas has the potential to increase trip generation and attraction, which in turn affects the performance of the surrounding road network. This condition needs to be examined, particularly in areas with relatively high traffic growth, such as Jl. Ir. PH. Moch. Noor, Murung Pudak District, Tabalong Regency. This study aims to evaluate existing traffic conditions and road performance, and subsequently compare them with the performance of the road network after the building becomes operational. The methods employed include traffic volume surveys on four road segments surrounding the development site, road capacity analysis based on the Indonesian Highway Capacity Guidelines (PKJI) 2023, and traffic projection modeling using trip generation (ITE), trip distribution (Furness method), and traffic assignment with the CONTRAM software. The results indicate that under existing conditions, road performance ranges from Level of Service (LOS) A to C. However, in the five-year post-operation projection, several road segments experience an increase in the degree of saturation, reaching LOS D, particularly on segments with the highest traffic volumes. The newly generated and attracted trips, combined with overall traffic growth, have the potential to degrade road performance if not accompanied by adequate traffic management and access control measures implemented by the facility operator to maintain the performance of the road network.